Multifocal radiculoneuropathy during ipilimumab treatment of melanoma. Issue 3 (27th July 2013) - Manousakis, Georgios; Koch, James; Sommerville, R. Brian; El‐Dokla, Ahmed; Harms, Matthew B.; Al‐Lozi, Muhammad T.; Schmidt, Robert E.; Pestronk, Alan
ABSTRACT Introduction: Ipilimumab, a monoclonal anti–CTLA‐4 antibody, is used to treat melanoma. Neuromuscular side effects, possibly autoimmune, may occur. Methods: In this investigation we undertook a retrospective review of patient records. Results: After 3 doses of ipilimumab, a 31‐year‐old man developed asymmetric, severe weakness involving all limbs, respiration, and cranial nerves, which was progressive over 2 weeks. EMG/NCS showed an axonal polyradiculoneuropathy with multifocal motor conduction blocks. CSF protein was 749 mg/dl. Nerve pathology showed inflammation around the endoneurial microvessels and subperineurial edema and inflammation. Spine MRI showed leptomeningeal and anterior and posterior root enhancement. Strength improved slowly over months after ipilimumab discontinuation and immunomodulating treatment. Conclusions: Ipilimumab toxicity presented as a monophasic, multifocal, asymmetric polyradiculoneuropathy involving roots and peripheral and cranial nerves. Ipilimumab may produce a polyradiculoneuropathy with disruption of the blood–nerve barrier due to a microvasculopathy. Muscle Nerve48: 440–444, 2013